2019
DOI: 10.1038/s41467-019-09418-0
|View full text |Cite
|
Sign up to set email alerts
|

FoxK1 and FoxK2 in insulin regulation of cellular and mitochondrial metabolism

Abstract: A major target of insulin signaling is the FoxO family of Forkhead transcription factors, which translocate from the nucleus to the cytoplasm following insulin-stimulated phosphorylation. Here we show that the Forkhead transcription factors FoxK1 and FoxK2 are also downstream targets of insulin action, but that following insulin stimulation, they translocate from the cytoplasm to nucleus, reciprocal to the translocation of FoxO1. FoxK1/FoxK2 translocation to the nucleus is dependent on the Akt-mTOR pathway, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 60 publications
(61 reference statements)
5
92
0
Order By: Relevance
“…After FOXK2 knockdown, we found that proliferation of GCs was inhibited and the numbers of apoptotic cells were increased. A similar result was reported in liver cells (Sakaguchi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…After FOXK2 knockdown, we found that proliferation of GCs was inhibited and the numbers of apoptotic cells were increased. A similar result was reported in liver cells (Sakaguchi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…A recent study linked FOXK2 to regulation of liver cellular proliferation and apoptosis via the PI3K-Akt pathway (Sakaguchi et al, 2019). In this study, we examined the role of FOXK2 knockdown on chicken GC proliferation and apoptosis.…”
Section: Foxk2 Promotes Granulosa Cell Proliferation Via Another Pi3kmentioning
confidence: 98%
See 1 more Smart Citation
“…It is made depletion of the motifs for Nr1i3 and Pit1, both of which are not expressed in human brain (Supplemental Figure 8c) [67,68]. When interpreting the multi-species liver model, in addition to the motifs that we found for the model trained on mouse sequences, we also found the motifs for additional TFs that are known to be involved in the liver, including Hnf4a [83][84][85], Foxk1 [86,87], Ets2 [88,89], Sp1 [90,91], Onecut1 [92,93], Bcl6 [94,95], and Nfe2l2 [96,97], as well as a depletion of the motif for Dbx1, which is not expressed in human liver [67,68], and a depletion of the motif for Zfp637 (Supplemental Figure 8d).…”
Section: Conservation Scoresmentioning
confidence: 84%
“…The balance of FOXO and FOXM1 transcription factors integrates Adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK)-mediated metabolic status and cell cycle regulation through competitive regulation of target genes (including Insulin-like growth factor-1 (IGF1)) in neonatal cardiomyocytes (11). FOXK1 and FOXK2 are important in the regulation of mitochondrial function, metabolism and apoptosis (12). FOXO family facilitated the cellular antioxidant defense, and on the other hand, ROS may regulate FOXO activity at many levels (13).…”
Section: Introductionmentioning
confidence: 99%